Defining a performance map of porous carbon sorbents for high-pressure carbon dioxide uptake and carbon dioxide–methane selectivity. Issue 38 (14th September 2016) - Ghosh, Saunab; Sevilla, Marta; Fuertes, Antonio B.; Andreoli, Enrico; Ho, Jason; Barron, Andrew R.
Abstract : The relative influence of heteroatom doping, surface area, and total pore volume of highly microporous carbon materials on CO2 uptake capacity, and the CO2 /CH4 selectivity, at high pressure (≤30 bar) is presented. Abstract : The relative influence of heteroatom doping, surface area, and total pore volume of highly microporous carbon materials on CO2 uptake capacity, and the CO2 /CH4 selectivity, at high pressure (≤30 bar) is presented. The separation of CO2 from natural gas (natural gas sweetening) is an important application that requires high CO2 uptake in combination with high CO2 /CH4 selectivity. Porous carbon (PC), N-doped PC (NPC), and S-doped PC (SPC) materials are prepared using KOH oxidative activation at different temperatures. The surface chemical composition was determined by XPS, while the surface areas, total pore volume, and pore size distributions were obtained by analyzing N2 adsorption–desorption isotherms with support from SEM and TEM. The CO2 and CH4 uptake was determined by volumetric uptake measurements (sorption and desorption). Contrary to previous proposals that N- or S-doping results in high uptake and good selectivity, we show it is the Σ(O, N, S) wt% that is the defining factor for CO2 uptake, of which O appears to be the main factor. Based upon the data analyzed, a performance map has been defined as a guide to designing/choosing materials for both future studies and large scale fluid bed applications using pelletized materials. For CO2 uptake at 30 bar any material with a surface area >2800 m 2 g −1 and a total pore volume >1.35 cm 3 g −1 is unlikely to be bettered. Such a material is best prepared by thermal activation between 700–800 °C and will have a carbon content of 80–95 wt% (as determined by XPS). While it has been assumed that the parameters that make a good CO2 adsorbent are the same as those that make a material with high CO2 /CH4 selectivity, our results indicate instead that for the best selectivity at 30 bar a surface area >2000 m 2 g −1 and a total pore volume >1.0 cm 3 g −1 and a carbon content of <90 wt% are necessary.